The influence of gender and social roles on academic achievement - Marques, Helena; Marcenaro-Gutiérrez, Óscar David; López-Agudo, Luis Alejandro (My University, 2016)
The analysis of the influence of certain social aspects across countries on gender differences in educational achievement has gained a great relevance. In this research the main objective is to deepen into the knowledge of these cultural factors. In order to accomplish this aim, international data from many countries has been used, grouped into education system characteristics, child qualities supported socially, views and opinions on gender roles, and risk-aversion attitudes. The empirical analysis carried out has shown that it is necessary to foster entrepreneurship attitudes during students’ tertiary education, with special emphasis on girls, as they are more affected by gender stereotypes and risk-aversion in comparison to boys. In spite of the existence of unexplained gender differences, individual and country-level factors may have a different effect on the academic achievement of boys and girls.
Keywords: Mujeres; Gender; Achievement; Institutions